Preparation of Phosphorus Speciation Reference Materials from Lake Sediments - YUAN Jian; WANG Ya-ping; XU Chun-xue (Yankuang ceshi, 2014)
Eutrophication in water bodies has a close relationship with the phosphorus speciation in sediments. The European Union developed the first reference material for phosphorus speciation of sediments BCR 684 in 2000 in order to determine accurately the contents of phosphorus speciation in sediments. However, supplies of BCR 684 are now exhausted. Moreover, the reference material of BCR 684 was collected from a lake in Europe which does not match the type and conditions of pollution in sediments in China. To this end, two phosphorus speciation reference materials of lake sediments (serial numbers: GBW 07462 and GBW 07463) on the fundamental of BCR 684, which were collected from Tai Lake, Jiangsu province and Dongting Lake, Hunan province in China, have been developed. The reference material was prepared by being dried, ground, sterilized and aged. Homogeneity and stability tests were conducted according to the JJG 1006—1994 and ISO Guide 35. For the homogeneity test, the variance test F value of 15 subsamples was less than the threshold value. During one year, four analysis results showed that there were no significant statistical changes in stability. The stability of the samples was checked twice in 2012 and 2013. The results show that the stability of the two reference materials is perfectly matched. Collaboration with eight laboratories was adopted in order to obtain certified value and uncertainty calculations. Parameter for certified values includes total phosphorus, inorganic phosphorus, organic phosphorus, apatite phosphorus and non-apatite phosphorus. SMT was used as the extraction method and the determined methods are molybdenum antimony anti Spectrophotometry and ICP-AES. BCR 684 was used as the quality control. The certified values and uncertainty were obtained under the JJG 1006—1994 and ISO Guide 35. These reference materials represent sediments in lakes with high eutrophication in China. The advantages of good representation of the sampling area, reasonable proxy selection and accurate certification values deem the reference materials suitable for quality monitoring of phosphorus speciation in sediments in the fields of environment, geology, agriculture and geochemistry.